2023
DOI: 10.1101/gad.350461.123
|View full text |Cite
|
Sign up to set email alerts
|

Structure and DNA-bridging activity of the essential Rec114–Mei4 trimer interface

Abstract: The DNA double-strand breaks (DSBs) that initiate meiotic recombination are formed by an evolutionarily conserved suite of factors that includes Rec114 and Mei4 (RM), which regulate DSB formation both spatially and temporally. In vivo, these proteins form large immunostaining foci that are integrated with higher-order chromosome structures. In vitro, they form a 2:1 heterotrimeric complex that binds cooperatively to DNA to form large, dynamic condensates. However, understanding of the atomic structures and dyn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…( F ) Model of Rec114 − Mei4 complex bound to two DNA duplexes. Residues implicated in DNA binding are shown as follows: R395, K396, K399, and R400 (4KR) in red ( Claeys Bouuaert et al 2021 ), and K403, K407, K417, and K424 in purple ( Liu et al 2023 ). The zoom only shows the position of the 4KR residues for clarity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…( F ) Model of Rec114 − Mei4 complex bound to two DNA duplexes. Residues implicated in DNA binding are shown as follows: R395, K396, K399, and R400 (4KR) in red ( Claeys Bouuaert et al 2021 ), and K403, K407, K417, and K424 in purple ( Liu et al 2023 ). The zoom only shows the position of the 4KR residues for clarity.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, residues K403/K407 and K417/K424 also participate in DNA binding ( Liu et al 2023 ). Residues K417 and K424 of one monomer contribute in trans to the DNA-binding surface composed of residues R395, K396, K399, R400, K403, and K407 (6KR) of the second monomer ( Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the majority of particles again had just a single copy of the Spo11 core complex. It remains to be determined whether inclusion of other accessory proteins such as Rec114 and Mei4 is needed to allow dimer assembly and DNA cleavage in vitro [41][42][43][44] .…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…The recent protein structure prediction revolution, spearheaded by AlphaFold2 [ 145 ] has considerably lowered the barriers to high-resolution structural information necessary for point mutant design. From this, separation-of-function mutants can be used to study the details of meiotic recombination, as has been demonstrated recently [ 63 , 108 , 110 ]. At the time of writing, advanced prediction algorithms like AlphaFold2 do not yet possess the capability to model post-translational modifications, small molecule ligands, or nucleic acids.…”
Section: Discussionmentioning
confidence: 99%